Greece–Turkey disaster diplomacy from disaster risk reduction. (August 2016) - Koukis, Theodore; Kelman, Ilan; Ganapati, N. Emel
Abstract: Disaster diplomacy examines how and why disaster-related activities do or do not reduce conflict and increase cooperation. The 1999 earthquakes in Greece and Turkey became an icon for this field of research, with numerous publications exploring how disasters might influence conflict. Fewer studies examine how disaster risk reduction might influence conflict. This paper presents a case study to explore disaster diplomacy for pre-disaster activities alongside post-disaster activities by discussing disaster risk reduction in Greece and Turkey in the context of Greek–Turkish governmental cooperation. The 1999 earthquakes are placed in context followed by an examination of disaster risk reduction in Greece and Turkey at multilateral, bilateral, and local levels. As with most disaster diplomacy case studies, disaster risk reduction for Greece and Turkey has not had a significant influence on the two countries' rapprochement.